La técnica del modelado para el desarrollo de la motricidad fina de los niños de inicial II, de la escuela Teniente Hugo Ortiz de la ciudad de Loja, periodo 2018-2019 - Quichimbo Sanmartin, Kely Mishel (2020)
The present research works the general objective was formulated to determine how the technique of modeling enhances the development of fine motor skills of children aged 4 to 5 years. Investigating the theoretical framework of the modeling technique for the development of fine motor skills. The methods used were: analytical, descriptive and deductive method. The techniques applied were the following: the interview that was applied to the teacher, the Tepsi test sheet which allowed diagnosing that 78% of the children had problems in fine motor skills. As a conclusion of the proposal based on modeling technique, it was evidenced that the motor level increased to 84% improving the control of fine movements through the modeling technique, concluding that this technique favors the development of fine motor skills. It is also considered that it should be applied from early ages in order to contribute to strength the development of visual-manual coordination that will enhance the reading-writing process.